Synergistic effects of high atmospheric and soil dryness on record-breaking decreases in vegetation productivity over Southwest China in 2023 - Zhikai Wang; Wen Chen; Jinling Piao; Qingyu Cai; Shangfeng Chen; Xu Xue; Tianjiao Ma (npj Climate and Atmospheric Science)
Abstract Extreme climate events have increasingly threatened global terrestrial ecosystems in recent decades. In spring 2023, Southwest China (SWC) experienced unprecedented heatwaves and droughts. Using multiple satellite-based datasets, we found that these events led to the most significant declines in gross primary productivity (GPP) and the enhanced vegetation index (EVI) for the past two decades, with lagged effects persisting until August in the drought-affected area. Unlike the widespread and persistent drought of 2010, the record-breaking heatwaves in April and May 2023 sustained and intensified the drought stress. Elevated temperatures and suppressed precipitation, driven by anomalous atmospheric circulations, exacerbated the soil moisture (SM) shortages and increased the atmospheric vapor pressure deficit (VPD), restricting water availability and carbon uptake for vegetation photosynthesis. Our findings reveal that, during the 2023 extreme event in SWC, the decreases in forest productivity were primarily driven by low SM anomalies, while the decreases in the grassland and cropland productivity mainly resulted from abnormally high VPDs. This study highlights the combined effects of low SM and high VPD anomalies caused by a compound heatwave–drought event on vegetation growth in SWC and provides valuable insights for future assessments of regional extreme climate events on vegetation growth.